National Breast Screening Programs across Europe - Peintinger, Florentia (Breast Care (Basel), 2019)
BACKGROUND: Mammography screening programs in Europe revealed a 25–30% breast cancer mortality reduction in women between 50 and 74 years. Early cancer detection and less radical treatment in dedicated multidisciplinary breast centers have improved breast cancer care. Breast population-based screening (persons are individually identified and personally invited to attend screening) is intended to detect breast cancer at an early stage to enable lower mortality rates. METHODS: The status of implementation of cancer screening programs among European countries, quality parameters and possible differences will be reviewed. RESULTS: Implementation of the recommended maximum age range was adopted in most programs. Almost all the European countries established digital mammography as the method of screening instead of screen-film mammography. Inequalities in implementation of cancer screening in the European Union have been observed. CONCLUSION: Improvement of data quality and mortality registries linked to the screening programs are needed.